Capacitor banks selection in radial distribution networks by combined algorithm - Zubiuk, Yu.; Trach, I.; Sevasjuk, I. (Технічна електродинаміка, 2015)
This paper presents the combined algorithm for determination of locations and sizes of capacitor banks in the radial distribution networks for practical minimization of power losses and costs of these losses and banks. The method of concessions and modified PSO-method are applied in the proposed algorithm. Additionally the technicalcoenosis criterion is applied for the specific account of technical and economic factors. The proposed approach allows to obtain the efficient practical solutions and increased stabilization of voltage profile in the radial distribution network.